Short tandem repeat based analysis of genetic variability in Munjal—the threatened sheep population of Northwestern India - YADAV, DINESH KUMAR; ARORA, REENA; BHATIA, S; SINGH, GURMEJ (The Indian Journal of Animal Sciences, 2011)
This paper examines the genetic variability at 25 microsatellite loci in Munjal - an important sheep of northwestern semi-arid region of India. Various genetic diversity estimates revealed high level of genetic variation within the investigated sheep population. The mean number of observed alleles (allele diversity) per microsatellite marker was 8.64 and that of effective alleles was 4.57. The average observed and expected heterozygosity (gene diversity) values were 0.712 and 0.744 respectively. The mean polymorphic information content value (0.721) further reflected high level of polymorphism across the loci. High heterozygosity values suggested low level of inbreeding and large number of alleles. Within the population, inbreeding estimate (FIS =0.034) further supported low level of inbreeding in the population. The Mode shift test showed that reduction in effective population size or a recent genetic bottleneck (40–80 generations) was unlikely in this sheep breed. Considerable level of genetic variability observed in the present study can be utilized in planning future breeding strategies of Munjal sheep especially in view of its threatened population status. In addition, information generated in the study can further be utilized for studying differentiation and relationships among different Indian sheep breeds for the selection of priority breeds at national level to maximize genetic diversity to be conserved for the benefit of future generations.